URGENSI PENGATURAN HUKUM CENTRAL BANK DIGITAL CURRENCY DALAM DIMENSI ANTI PENCUCIAN UANG - Lisanawati, Go; Aristo, Erly (Faculty of Law, Parahyangan Catholic University, 2022)
The issue of digitalized forms of payment systems has required adjustment from a State to accomodate and respond. One of the issues is concerning the use of virtual currencies, and Central Bank Digital Currency. It requires the accomodative and responsive of the law instruments in Indonesia to arrange that issue. The payment systems’ policy in Indonesia has not placed any issues of crypto/digital currency as one of the payment methods. Central Bank Digital Currency is a the digital form of fiat money. Through the Bank Indonesia Regulation Number 18/40/PBI/2016 concerning Operation of Payments Transaction Processing, and Bank Indonesia Regulation Number 19/12/PBI/2017 concerning the Implementation of Financial Technology, it can be understood that Indonesia remain bans the use of any virtual currency as payment instruments. Central Bank Digital Currency has different form of virtual currencies which are not issued by the state, but it is remain called as virtual currencies. In fact, the use of virtual currencies has been exploited by money launderer to do laundering. Virtual currencies has no underlying asset or responsible authority or administrator, volatile, risky, and speculative. This article is a normative legal research method that will analyzed the direction in which Indonesian Law can headed Central Bank Digital Currency while the option has become more less for not response it. The result of this research has showed that it is urgently need for Bank Indonesia (as a central bank in Indonesia) to recognise Central Bank Digital Currency as payment’s instrument.